Characteristics of veterans receiving buprenorphine vs. methadone for opioid use disorder nationally in the Veterans Health Administration. (1st March 2016) - Manhapra, Ajay; Quinones, Lantie; Rosenheck, Robert
Highlights: Limited knowledge about agonist treatment choice for opioid use disorder in practice. Compared characteristics of veterans on buprenorphine vs methadone nationally. The choice was shaped by demographic characteristics rather than clinical factors. We also found significant race based variations in choice of agonist therapy. Abstract: Background: The advent of buprenorphine as an alternative to methadone has dramatically shifted the landscape of opioid agonist therapy (OAT) for opioid use disorder (OUD). However, there is limited US national level data describing thedifferences between patients who are prescribed these two OAT options. Methods: From veterans with OUD diagnosis who used Veterans Health Administration services in 2012, we identified 3 mutually exclusive groups: those who received (1) buprenorphine only ( n = 5, 670); (2) methadone only ( n = 6, 252); or (3) both buprenorphine and methadone in the same year ( n = 2513). We calculated the bi-varate effect size differences (risk ratios and Cohen's d) forcharacteristics that differentiated these groups. Logistic regression analysis was then used to identify factors independently differentiating the groups. Results: Ten year increment in age (OR 0.67; 95% CI 0.64–0.70), urban residence (OR 0.26; 95% CI 0.25–0.33), and black race (OR 0.39; 95% CI 0.35–0.43) were strongly and negatively associated with odds of receiving buprenorphine compared to methadone, while medical and psychiatric comorbidities or receipt of other psychiatric medications did not demonstrate substantial differences between groups. Conclusions: Differences between veterans receiving buprenorphine or methadone based OAT seems to be largely shaped by demographic characteristics rather than medical or psychiatric or service use characteristics. A clearer understanding of the reasons for racial differences could be helpful in assuring that black OUD patients are not denied the opportunity to receive buprenorphine if that is their preference.